Technical report: Euler Lagrange Equation for the unmanned hovercraft / Nor Syahirah Mazeli, Nurfarahin Suzairy and Amira Awatif Ismail - Mazeli, Nor Syahirah; Suzairy, Nurfarahin; Ismail, Amira Awatif (2017)
There are many electrical and mechanical systems that are used in agriculture operations, oil rigs and border patrol in order to increase the quality of human life. Hovercraft is a vehicle that can help to overcome the worst condition such as floods, earthquakes, nuclear reactors and others which is normally faced by human nowadays. This vehicle can move on land and water surfaces and it also consist of air cushion which has air compressed inside. This research paper focuses on hovercraft model that based on Euler Lagrange Equation. We used Maple software to solve the model of the hovercraft. Then, we used MATLAB/Simulink environment to test the stability of the model with open loop and closed loop simulations. Lastly, we show our results using graphs.